Estimated Glomerular Filtration Rate and Sleep Quality in Stage 3-5 Non-Dialysis Chronic Kidney Disease Patients: Is There a Correlation? - Umboh, Octavianus; Palar, Stella; Moeis, Emma Syarifih (PERNEFRI (PERHIMPUNAN NEFROLOGI INDONESIA), 2024)
Background: Chronic kidney disease (CKD) is a growing health issue that significantly affects patients' quality of life. CKD patients are prone to sleep disturbances, which can lead to chronic fatigue and a decrease in their quality of life. The Pittsburgh Sleep Quality Index (PSQI) is a parameter that can be used to assess the sleep quality of CKD patients. Objective: This study aims to determine the relationship between estimated glomerular filtration rate (eGFR) and sleep quality in non-dialysis CKD patients. Methods: The research design is an observational analytic study with a cross-sectional approach. The research subjects were stage 3-5 non-dialysis CKD patients aged 18 to 60 years at Prof. Dr. R. D. Kandou Hospital Manado from March to May 2022. The sleep quality of CKD patients was assessed using the PSQI score. Data analysis was performed with a significance level of p < 0.05. Results: A total of 30 patients with stage 3-5 non-dialysis CKD were found. They consisted of 20 males and 10 females, aged 38-59 years, with an average of 59.80 ± 9.86 years. In the normality test using Shapiro-Wilk, the patient samples were not normally distributed (p = .000). For statistical analysis using the Spearman test, a negative correlation was found between eGFR and PSQI scores (r = -0.554), which was statistically significant (p = 0.002). Conclusion: This study found a significant relationship between eGFR and PSQI scores, which shows that a decrease in eGFR worsens the sleep quality of non-dialysis CKD patients.